Margaret Thornton, dissonance and distrust: women in the legal profession - E. Cowdery (Law Text Culture, 1997)
In Dissonance and Distrust: Women in the Legal Profession, Margaret Thornton provides a compelling theoretical account of the continuing resistance to the participation of women as legal professionals, despite their increased presence in law schools and in some areas of legal practice. She suggests that women are still 'fringe-dwellers in the jurisprudential community' (Thornton 1996: 3-4) and will remain so until it is recognised that the issue is not simply one of women being 'let in' to the profession in equal numbers to men, but also involves posing fundamental questions about the character and constitution of law as it is taught and practised.